Requirements high commitment management to achieve entrepreneurship strategic in busness organization / Field research in Iraqi construction companies - النعيمي شهاب الدين حمد; حميد ريم مهند (Journal of Economics and Administrative Sciences, 2015)
This research came to shed light on the relationship between the requirements of (practices) high commitment management (participative decision making،information sharing، training and development،team working،rewards،selective staffing،job security ) and strategic entrepreneurship dimensions (entrepreneurial culture،entrepreneurial leadership،entrepreneurial mindset، strategic management resources ) Sought to achieve the number of goals the knowledge and applied, and tested the relationship and impact between variables in a sample size of 100 directors of personnel departments and divisions and their associates in the Iraqi contractors in Baghdad (Hamorabi، Mutassim، AL Rasheed، AL Mansour )، focused research problem is the existence of a distinct lack of application high commitment management human resources and how to employ in order to ensure the achievement of strategic enterpreneurship in construction companies Iraq، and data analysis research used statistical ready (SPSS) and program (Excel )، is the most important statistical tools in analysis of the mean deviation normative and coefficient of variation and spearman correlation.the main findings of the existence of a correlation and impact between the high commitment management and strategic entrepreneurship ، his included four research axes went to the first systematic and theoretical framing of the second and third to view and analyze the results and hypothesis testing in the fourth devoted to the conclusions and recommendations